Bioactive structural basis of proteoglycans from Sarcandra glabra based on spectrum-effect relationship. (15th September 2020) - Sun, Xuyang; Zhao, Qianqian; Si, Yu; Li, Kaidong; Zhu, Jingyi; Gao, Xiangdong; Liu, Wei
Abstract: Ethnopharmacological relevance: Proteoglycans are one of the active ingredients of great importance in Sarcandra glabra . The biological activities of proteoglycans extracted from Sarcandra glabra including suppressing tumor growth and antioxidant activity were studied. However, raw materials from different regions may cause differences in the activity of natural extracts, especially for bioactive biomacromolecules. Conventional identification of S.glabra cannot accurately reflect the distinguishing relationship between internal components and the pharmacological activity. The identification of biologically active structures was obtained by constructing multiple fingerprint and spectrum-effect relationship. Aim of the study: To evaluate the bioactive structural basis of proteoglycans from S.glabra based on spectrum-effect relationship and chemometric methods. Materials and methods: Multiple fingerprinting including HPSEC, PMP-HPLC, and FT-IR of proteoglycans was established from 18 batches of samples based on the structural characteristics. Both antitumor activity and antioxidant activity were determined. Mathematical analysis was used to analyze the spectrum-effect relationship. Results: PCA results showed monosaccharides including Xly, Rha, and GlcA, carboxyl group in acidic sugars, peptide bond in proteins, and methylene groups could be used as markers for distinguishing the samples from different sources. The results of the spectrum-effect relationship analysis indicated that the bioactive markers of inhibitory activity on MG63 and U2OS cells by PLS-DA were related to GlcA, Xyl, Fuc, β-glycosidic bonds, peptide linkage, and methylene groups. Markers composing monosaccharide for antioxidant activity were Xyl, GlcA, and GlcN. Meanwhile, the group markers were pyranose ring, carboxyl group, peptide linkage, and methylene structure. Conclusions: The material basis that affects the pharmacological efficacy could be found according to the spectrum-effect relationship analysis. This study could lay a foundation for further exploring the relationship between structural characteristics and pharmacodynamics of macromolecular glycoconjugates in Traditional Chinese Medicine. Graphical abstract: Image 1 Highlights: Multiple fingerprinting of proteoglycans from Sarcandra glabra was established. The spectrum-effect relationship was analyzed by PLS-DA model. Monosaccharide and functional group markers were obtained.